WORKSHOP APLIKASI DASHBOARD INTERNAL SDM DENGAN MENGINTEGRASIKAN KNIME DAN APPSHEET DI KPP PMA SATU KALIBATA - Yulhendri Yulhendri (Nindikayla Institute, 2023)
This workshop is aimed at providing participants with the skills to create internal HR dashboard applications without the need for programming or coding skills. The workshop will cover the creation of internal HR dashboard applications using KNIME and Appsheet for android platforms, integrating data from various sources, and displaying data in an easily readable and understandable format. The methods used include direct learning, group discussions, and independent practice. Participants who can attend this workshop include HR staff, HR managers, or other staff who wish to learn how to create internal HR dashboard applications. Through this workshop, participants will benefit from being able to create internal HR dashboard applications without the need for programming or coding skills, managing HR data more effectively and efficiently, and increasing the effectiveness of HR management in the organization